TAFSIR FENOMENOLOGI SIMBOLIK AL-QUR’AN - Ahmad Suhendra, Nunung Lasmana dan (IAIN Kediri, 2015)
the QurÃ¢â‚¬â„¢anic studies in Indonesia continue to experiencing a significant growth. Lukman Abdul Qohar Sumabrata,Ã‚Â Lukman Saksono, and Anharudin offered a symbolic method of interpretation. They seek to interpret the QurÃ¢â‚¬â„¢anÃ‚Â with different perspectives by looking at its format and structure, leading to different interpretations of theÃ‚Â QurÃ¢â‚¬â„¢an. Lukman Abdul Qahar SumabrataÃ¢â‚¬â„¢s interpretation method attracted attentions from many people andÃ‚Â encouraged them to study more closely the format and structure of the QurÃ¢â‚¬â„¢an. The interpretation of symbolicÃ‚Â phenomenology refers to the format and structure of the QurÃ¢â‚¬â„¢an of the Ã¢â‚¬ËœUthmÃ„Âni script.Keywords: al-QurÃ¢â‚¬â„¢an, Fenomenologi Simbolik, Tafsir